Challenges in the Implementation of Consumer Legal Protection in Indonesia: A Case Study on Regulatory Gaps and Enforcement Issues - R.Tomelo, Aprillia (Estudiante Law Journal, 2025)
Legal protection for consumers is important in maintaining consumer rights in the market. The purpose of this study is to analyze the form of legal protection provided to consumers and the obstacles faced in its implementation. The method used is a descriptive approach with a case study, where data is collected through observation and interviews with consumers and business actors. The results show that although there are regulations governing consumer protection, there are still obstacles in its implementation, such as lack of consumer awareness and weak supervision from the authorities. Effective legal protection is needed to ensure fairness and consumer welfare in economic transactions.